A SYSTEMATIC LITERATURE REVIEW ON PROJECT-BASED LEARNING IN PRIMARY EDUCATION - Atmojo, Setyo Eko; Hana Arikah, Hana Arikah; Aryan Trisna Wibisono, Aryan Trisna Wibisono; Noor Muktiningrum, Noor Muktiningrum; Alifah Nisa Azzahra, Alifah Nisa Azzahra; Estri Mariana, Estri Mariana (Dialektika Jurnal Pendidikan, 2026)
This study aims to analyze the development, characteristics, impacts, and challenges of implementing Project Based Learning (PjBL) in primary education. The method used is a Systematic Literature Review (SLR) employing the PRISMA approach through an analysis of 25 articles from national and international journals spanning the years 2016–2026. The results of the study indicate that the use of PjBL has increased significantly and is widely applied across various subjects. PjBL has been proven to improve learning outcomes as well as 21st-century skills such as critical thinking, creativity, communication, and collaboration. However, its implementation still faces challenges such as time constraints, teacher readiness, and supporting resources. Therefore, optimal planning and support are necessary to ensure the effective implementation of PjBL.